2018
DOI: 10.1177/1947603518812555
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Cartilage Repair from Marrow Stimulation Correlates with Cell Number, Clonogenic, Chondrogenic, and Matrix Production Potential of Underlying Bone Marrow Stromal Cells in a Rabbit Model

Abstract: Objective Previous studies have shown that intrinsic behavior of subchondral bone marrow stem cells (BMSCs) is influenced by donors and locations. To understand the variability in cartilage repair outcomes following bone marrow stimulation, we tested the hypothesis that in vivo cartilage repair correlates with in vitro biological properties of BMSCs using a rabbit model. Methods Full-thickness cartilage defects were created in the trochlea and condyle in one knee of skeletally mature New Zealand White rabbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Earlier studies have shown that PRP can induce a significant improvement in BMSC recruitment, angiogenesis (Simpson, Mills, & Noble, ; Veillette & McKee, ), expression of cartilage matrix (Smyth, Murawski, Fortier, Cole, & Kennedy, ), proliferation, and viability of chondrocytes and BMSCs (Lee, Park, Joung, Park, & Do, ; Park, Lee, Kim, Ahn, & Do, ) as well as stimulate migration and chondrogenic potential of subchondral BMSCs (Kruger et al, ). A strong influence of properties and potential of bone‐marrow‐derived stem cells in influencing cartilage repair has been demonstrated in the earlier studies (Dwivedi, Chevrier, Alameh, Hoemann, & Buschmann, ; Dwivedi, Chevrier, Hoemann, & Buschmann, ). Using an ovine chronic‐defect model, Milano et al showed that when used as an adjunct to BMS, PRP enhanced the repair response versus BMS alone (Milano et al, ).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Earlier studies have shown that PRP can induce a significant improvement in BMSC recruitment, angiogenesis (Simpson, Mills, & Noble, ; Veillette & McKee, ), expression of cartilage matrix (Smyth, Murawski, Fortier, Cole, & Kennedy, ), proliferation, and viability of chondrocytes and BMSCs (Lee, Park, Joung, Park, & Do, ; Park, Lee, Kim, Ahn, & Do, ) as well as stimulate migration and chondrogenic potential of subchondral BMSCs (Kruger et al, ). A strong influence of properties and potential of bone‐marrow‐derived stem cells in influencing cartilage repair has been demonstrated in the earlier studies (Dwivedi, Chevrier, Alameh, Hoemann, & Buschmann, ; Dwivedi, Chevrier, Hoemann, & Buschmann, ). Using an ovine chronic‐defect model, Milano et al showed that when used as an adjunct to BMS, PRP enhanced the repair response versus BMS alone (Milano et al, ).…”
Section: Introductionmentioning
confidence: 63%
“…Taken together, these factors may drive the superior repair response in presence of CS/PRP implants indicated by more hyaline nature of repair accompanied by better macroscopic regeneration and increased bone remodelling. Because the cartilage repair outcome is strongly influenced by the properties of BMSCs including their number, proliferation, and chondrogenic potential (Dwivedi, Chevrier, Alameh, et al, ), application of CS/PRP is also likely to improve the cartilage repair outcome with poor prognosis arising due to low cell number or reduced chondrogenic potential in older patient population or patients with older defects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MSCs present in the SB are accessible through subchondral plate perforation and are believed to be responsible for limited cartilage regeneration following microfracture treatment of focal cartilage lesions (Dwivedi et al, 2018). In our previous work, we investigated SB MSCs in advanced knee OA and compared MSCs from the medial, commonly weight-bearing compartment, with the lateral side of the joint (Sanjurjo-Rodriguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although cell dosages have been associated with morphological quality of repair tissue in cell-based procedures, 12,33 absence of dosage effect while demonstrating safe and efficient treatment has been shown up to 4 years for the current clinical trial. 4,[37][38][39] Here, we present the final assessment of the full study duration of 5 years.…”
mentioning
confidence: 99%